Rational synthesis of Ni nanoparticle-embedded porous graphitic carbon nanosheets with enhanced lithium storage properties. Issue 43 (20th October 2015) - Zhang, Jingfei; Zhu, Huimin; Wu, Ping; Ge, Cunwang; Sun, Dongmei; Xu, Lin; Tang, Yawen; Zhou, Yiming
Abstract : We present a facile and scalable synthesis of Ni nanoparticle-embedded two dimensional (2D) porous graphitic carbon nanosheets, which manifests outstanding lithium storage properties. Abstract : Carbon-based materials have recently received increased attention as very promising anode materials for rechargeable lithium-ion batteries (LIBs) because of their non-toxicity, low cost, and excellent performances. Nanostructure engineering has been demonstrated as an effective approach to improve the electrochemical performance of electrode materials. Here, we present a facile and scalable synthesis of two-dimensional (2D) porous graphitic carbon nanosheets embedded by numerous homogeneously dispersed Ni nanoparticles. With both structural and compositional advantages, the as-synthesized nanohybrid manifests a very stable high reversible capacity of 740 mA h g −1 after 100 cycles at a current density of 100 mA g −1, and also excellent rate capability and cycling stability. We believe that the synthetic strategy outlined here can be extended to other rationally designed anode materials with high performances in LIBs.